The evolving impact of labour markets on monetary policy - Sławiński, Andrzej; Hausner, Jerzy (Journal of Public Governance, 2019)
Objectives: The aim of this paper is to address the cycle from monetary policy becoming the main instrument of macroeconomic stabilisation to the current unexpected decline in its effectiveness. Research Design and Methods: This article analyses how preventing the risk of wage-price spirals unwinding became the main task of central banks. Such a perception of monetary policy role was a natural consequence of the Great Inflation of the 1970s and the substantial costs of disinflation of the 1980s. Then this paper highlights the causes behind the recent unexpected emergence of persistently low inflation. Among the most important causes of this were structural changes which took place also in labour markets, being the outcome of the twilight of traditional manufacturing and increasing globalisation. Findings: The structural weakening of the bargaining position labour creates situation in which the period when monetary policy was focused on preventing wage-price spirals has ended. If advanced economies are entering a long period of low inflation and low interest rates, it will necessitate a reformulation of the role that central banks play in stabilisation policies. Recommendation: This paper postulates that central banks should acquire a pivotal role in the macroprudential policy. The main argument is that the independence of central banks, which they obtained when fighting inflation, would increase the effectiveness of the macro-prudential policy. Contribution: Usually success in lowering and stabilising inflation is attributed mainly to the changes in the way in which central banks have been conducting their monetary policy since the early 1980s. This article highlights the fact that the role which was played in this process by the substantial weakening of the labour bargaining position is still underappreciated.